Efficient Generation of Polarization-Entangled Photons in Metal-Organic Framework Waveguides - Herrera-Urbina, F; Fritz, R (Optica Publishing Group (formerly OSA), 2024)
Parametric nonlinear optical processes are instrumental in optical quantum technology for generating entangled light. However, the range of materials conventionally used for producing entangled photons is limited. Metal-organic frameworks (MOFs) have emerged as a novel class of optical materials with customizable nonlinear properties and proven chemical and optical stability. The large number of combinations of metal atoms and organic ligand from which bulk MOF crystals are known to form, facilitates the search of promising candidates for nonlinear optics. To accelerate the discovery of next-generation quantum light sources, we employ a multi-scale modeling approach to study phase-matching conditions for collinear degenerate type-II spontaneous parametric down conversion (SPDC) with MOF-based one dimensional waveguides. Using periodic-density-functional theory calculations to compute the nonlinear optical properties of selected zinc-based MOF crystals, we predict polarization-entangled pair generation rates of order 104 − 107 s−1mW−1 at 1064 nm for 10 mm crystals, improving the brightness of industry materials such as PPKTP and BBO in some cases. This work underscores the great potential of MOF single crystals as entangled light sources for applications in quantum communication and sensing. © 2024 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement.